Glutamate and 2-amino-4-phosphonobutyrate evoke an increase in potassium conductance in retinal bipolar cells. - Hirano, A A (1991)
Although there is general agreement that L-glutamate can produce a depolarizing inward current to account for the hyperpolarizing (OFF) bipolar cell response, the conductance mechanism underlying the depolarizing (ON) response has been difficult to establish satisfactorily. To investigate the ionic bases of the center responses, we studied the whole-cell currents controlled by L-glutamate and its analogues in solitary bipolar cells from salamander retina. We report here two groups of isolated bipolar cells: one group responded to L-glutamate with the previously described inward current [Attwell, D., Mobbs, P., Tessier-Lavigne, M. & Wilson, M. (1987) J. Physiol. (London) 387, 125-161] and a second group showed an outward current that reversed at about -70 mV. Both were associated with an increase in membrane conductance. In addition, DL-2-amino-4-phosphonobutyrate, a compound diagnostic for ON-bipolar cell activity [Slaughter, M. M. & Miller, R. F. (1981) Science 211, 182-185], elicited outward currents that closely resembled those seen in response to L-glutamate and, furthermore, that were shown to arise from an increase in conductance to potassium ions. Thus the presence of two distinct conductances controlled by L-glutamate in solitary cells would provide one mechanism for generating the ON and OFF light responses at the bipolar cell level in the intact retina.